The impact of adenotonsillectomy on the acoustic parameters of voice - Shetti, Preeti S.; Bhat T., Mahesh; Fernandes, Jacqueline B.; Saxena, Tanishtha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: The aim of the study was to evaluate and compare the changes in the acoustic parameters of voice and nasalance in individuals with chronic adenotonsillitis, before and after surgery. Methods: A pospective case-control study conducted in the department of ENT and HNS of a tertiary care centre from September 2014 to June 2016 with 120 patients aged between 5 to 16 years. 60 cases and 60 controls were assessed aged between 5 to 16 years. Cases included patients who underwent adenotonsillectomy in the inpatient department of ENT at Father Muller Medical College, Mangalore, India. Acoustic analysis of 5 parameters (fundamental frequency, jitter, shimmer, noise harmonic ratio and nasalance) was done 1day pre-operatively and at 4 weeks post-operatively by means of a VAGMI, Voice and Speech Systems, Bangalore, India, providing normative data for analysed measures. Results: The results of the study showed that pre-operative cases exhibited significant alterations in Jitter, Shimmer and NHR, compared to the control group. No significant differences were observed in the F0. Nasalance significantly reduced post-operatively and were almost normalized after the surgery. Conclusions: Chronic adenotonsillar hypertrophy causes transient changes in acoustic parameter of voice, which makes the voice disharmonic and harsh. Adenotonsillectomy eliminates the nasalance. Hence, parents should be warned for changes in voice after surgery.